2008
DOI: 10.1111/j.1742-7843.2008.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effect of the Polygala sabulosa Hydroalcoholic Extract in Mice: Evidence for the Involvement of Glutamatergic Receptors and Cytokine Pathways

Abstract: This study investigated the role of the glutamatergic system on the antinociception caused by Polygala sabulosa hydroalcoholic extract (HE). The systems mediated by substance P, capsaicin, interleukin-1 β (IL-1 β ) and tumour necrosis factor-α (TNF-α ) were also investigated. P. sabulosa HE given orally produced a significant inhibition of glutamateinduced paw licking ) mg/kg and inhibition of 79 ± 6% at 1000 mg/kg]. The plant derivatives α -spinasterol, scopoletin and styryl-2-pyrones (compound 1 and 3) (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…Only the Dcm fraction and ␣-spinasterol reduced edema formation and spontaneous nociception. Our results are in accordance with previous findings that demonstrated that ␣-spinasterol exerted antinociceptive effects in different acute pain models, including glutamate-mediated spontaneous nociception and acetic acid-induced abdominal constriction (Meotti et al, 2006;Ribas et al, 2008;Freitas et al, 2009). However, the mechanisms underlying the antinociceptive effect of ␣-spinasterol remain to be elucidated.…”
Section: Discussionsupporting
confidence: 83%
“…Only the Dcm fraction and ␣-spinasterol reduced edema formation and spontaneous nociception. Our results are in accordance with previous findings that demonstrated that ␣-spinasterol exerted antinociceptive effects in different acute pain models, including glutamate-mediated spontaneous nociception and acetic acid-induced abdominal constriction (Meotti et al, 2006;Ribas et al, 2008;Freitas et al, 2009). However, the mechanisms underlying the antinociceptive effect of ␣-spinasterol remain to be elucidated.…”
Section: Discussionsupporting
confidence: 83%
“…Particularly, a mechanism for synaptic potentiation involves NMDA receptors located in peripheral structures, spinal cord and above these, when activated, increase synaptic transmission between nociceptive afferent fibres and dorsal horn neurons . Additionally, activation of these receptors can stimulate the production of a variety of intracellular second messengers such as nitric oxide and pro‐inflammatory cytokines, which act synergistically in the excitation of neurons . In the present study, myrtenol produced an inhibition of the nociception induced by glutamate, suggesting that the inhibition of this signalling pathway is involved in the antinociceptive effect of this compound.…”
Section: Discussionsupporting
confidence: 50%
“…It is well established that glutamate is involved in the transmission of nociceptive signals from the peripheral nervous system to the dorsal horn of the spinal cord. Moreover, it has been reported that glutamate injection evoked pronounced nociceptive responses, which are mediated by neuropeptides (Substance P) releasing from C fibers and due to activation of glutamate receptors [i.e., N-methyl-d-aspartic acid (NMDA)] that can stimulate the production of a variety of intracellular second messengers, such as NO, and proinflammatory cytokines as tumor necrosis factor-alpha (TNF-α) and IL-1β, which act synergistically in the excitation of the neurons (Ribas et al, 2008). Additionally, Beirith et al (2002) have found that the nociceptive response induced by glutamate appears to involve peripheral, spinal, and supraspinal sites of action and is greatly mediated by both NMDA and non-NMDA receptors.…”
Section: Resultsmentioning
confidence: 99%